The prehistory of the peoples of the Iberian Peninsula: “genetic intervention” of the early pyramid period - Alexander A. Orlov (Ибероамериканские тетради)
Recently, the American geneticist David Reich, according to the results of studies, got by his group, published a hypothesis that 4.5 thousand years ago, the Iberian Peninsula was conquered by the tribes of nomadic pastoralists who came from the steppes of Eastern Europe, by so-called “people of the Yamnaya culture” (the Yamnaya people). Having a higher technological level (had four-wheeled carts, domesticated horses, etc.), those people quickly conquered the Iberian tribes, completely eliminating or enslaving the entire male autochthonous population. Such a rapid and, apparently, far from peaceful expansion led to the fact that the next generation of residents of the Iberian Peninsula had already 100% Y chromosomes (which are transmitted exclusively through the paternal line) of immigrants. The Yamnaya people brought their culture to the Peninsula, and probably the IndoEuropean language, the carriers and distributors of which they were, migrating across the expanses of Europe.